Diagnóstico de Babesia bovis y Bavesia bigemina en las ganaderías del sector oeste de la provincia de Zamora Chinchipe, mediante los métodos de GIEMSA y reacción en cadena de la polimerasa. - Benítez Miranda, Daniel Alberto (2017)
In the present research a total of 96 bovine blood samples of cattle from the west sector in the province of Zamora Chinchipe were analyzed using the Giemsa staining method and the prevalence of Babesia spp. in this sector is 36.4%; It was determined by cantons, in the canton Zamora is 39.7%, and the prevalence in the canton Centinela del Cóndor is 26.1%; In terms of prevalence by gender, in females was 37.8% and 28.6% in males; in relation to age, animals older than 4 years were prevalent in 50%, animals between 1 and 2 years old were 47.4%, animals between 3 and 4 years old were 29%, and in animals less than one year the prevalence was 22.7%; With respect to breeds in the Gyr breed the prevalence was 66.7%, in the crossbred was 44.2%, in the Holstein was 32.4%, in the Brown Swiss was 22.2%, and in the Charolais was 14.3%. Of the 96 samples, 70 were selected which were processed by the nPCR methods in order to determine the prevalence of B. bovis and B. bigemina, where the overall prevalence is 81.7%, B. bigemina was 68.5% and B. bovis was 61.4%; with respect to the cantons, it was determined that the prevalence in the canton Zamora was 90.7% and in Centinela del Cóndor was 75%; In terms of gender, the prevalence in females was 88.3% and in males was 80%; regards to age in animals between 3 and 4 years was 95.2%, in less than 1 year was 86.7%; in animals between 1 and 2 years was 83.3%; in animals older than 4 years was 81.2%; towards breeds, the Charolais breed was 100%, the crossbred was 91.9%, the Holstein was 88.9%, the Brown Swiss was 66.7% and the Gyr was 33.3%.